2021
DOI: 10.1111/jora.12639
|View full text |Cite
|
Sign up to set email alerts
|

Moral Development in Adolescence

Abstract: This article provides a selective review of research on moral development in adolescence during the past decade. We begin with introducing key concepts and reviewing critical theoretical advances in the field of adolescent moral development. This includes integrative models to the developmental study of morality and dynamic socialization models of moral development. Next, related major empirical findings are presented on moral emotion–behavior links, morality in intergroup contexts, and the socialization of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 169 publications
1
10
0
1
Order By: Relevance
“…It could be argued that low contact willingness represents the behavioral conversion of adolescents’ ethnic prejudice, while helping intentions might tap into the general domain of prosociality rather than being a measure of behavioral prejudice per se. Prior research has confirmed the strong associations between empathic competences and prosocial behaviors (e.g., Metzger et al, 2018 ; Van der Graaff et al, 2018 ; for a review, see Malti et al, 2021 ), and might therefore explain the unique inverse reciprocal links observed in the current study among empathic concern and low helping intentions.…”
Section: Discussionsupporting
confidence: 76%
“…It could be argued that low contact willingness represents the behavioral conversion of adolescents’ ethnic prejudice, while helping intentions might tap into the general domain of prosociality rather than being a measure of behavioral prejudice per se. Prior research has confirmed the strong associations between empathic competences and prosocial behaviors (e.g., Metzger et al, 2018 ; Van der Graaff et al, 2018 ; for a review, see Malti et al, 2021 ), and might therefore explain the unique inverse reciprocal links observed in the current study among empathic concern and low helping intentions.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, young children are more likely to experience pride due to physical characteristics (e.g., height), whereas adolescents are more likely to attribute pride to interpersonal moral traits (e.g., being friendly, well-respected, and helpful; Rosenberg, 1979). This shift may also be due to the development of children’s self-concepts, such that, with age, children begin to focus more on growing toward their ideal self (Krettenauer & Stichter, 2023; Malti et al, 2021). As a result, older children and adolescents become sensitive to positive outcomes that are in line with their self-ideals and thus more likely to experience moral pride.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results suggest that SES background is equally relevant for boys as well. Although the literature suggests that STEM-gender stereotypes are more prevalent among adolescents than younger children due to advanced cognitive abilities connecting their identity with social categories (e.g., Passolunghi et al, 2014 ; Miller et al, 2018 ; Starr and Simpkins, 2021 ), however, other changes related to critical and moral skills could be generally associated with lower levels of STEM-gender stereotypes (e.g., Malti et al, 2021 ). A higher SES background could foster such skills for both girls and boys, and this could more easily explain our findings showing a lack of gender differences.…”
Section: Discussionmentioning
confidence: 99%